The factors affecting employee’s satisfaction at Northport (Malaysia) Bhd / Norhaniza Ya-Habib and Natrah Hamzah - Ya-Habib, Norhaniza; Hamzah, Natrah (Faculty of Business and Management, 2013)
Employee satisfaction is important in managing human capital in the organization. The purpose of this study was to determine the relationship between employee’s satisfaction, work environment, services satisfaction and training opportunities. Theoretical framework was developing based on the detailed-on literature review. Simple random sampling can be as sampling technique. A total of 132 samples were taken for the direct reports revealed that work environment, services satisfaction and training opportunities factors was positively and significantly related to the employee’s satisfaction. We discuss the recommended that suitable for our research and also for company to enhance their employee satisfaction.